2016
DOI: 10.1111/ijpo.12144
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls of the self‐regulation of advertisements directed at children on Mexican television

Abstract: Despite the self-regulation of television marketing, children were surrounded by UFB advertisements. Signatory companies influence children indirectly by targeting other audiences and by marketing during family television programs, which are also watched by children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…In the largest study to date, we analysed 250 children's movies to explain the depiction of healthy, unhealthy, and mixed beverages and foods over the past 25 years. We confirm findings from previous research that media content targeted at children is dominated by energy‐dense and nutrient‐poor foods . Even more importantly, our study is the first to demonstrate that unhealthy foods and beverages are more likely to be presented centrally, to be evaluated positively, to be interacted with, and to be consumed in children's movies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the largest study to date, we analysed 250 children's movies to explain the depiction of healthy, unhealthy, and mixed beverages and foods over the past 25 years. We confirm findings from previous research that media content targeted at children is dominated by energy‐dense and nutrient‐poor foods . Even more importantly, our study is the first to demonstrate that unhealthy foods and beverages are more likely to be presented centrally, to be evaluated positively, to be interacted with, and to be consumed in children's movies.…”
Section: Discussionsupporting
confidence: 89%
“…It is, therefore, of great importance to understand the ways in which foods and beverages are presented in media targeted at children. Previous research has shown, for instance, that TV commercials for children are very likely to depict foods high in salt, fat, and sugar . Other research has focused on foods embedded in editorial content such as television programming .…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect to consider is the concurrent introduction of an 8% ad valorem tax to nonessential energy dense food that has shown to be associated with purchases (27). It is also possible that differential changes in purchases of taxed beverages may result not only due to the elastic nature of the demand for SSB, but it could also be the result of more awareness about the negative effect of SSBs on health (10) and of recommendations by WHO/PAHO to reduce the intake of SSBs through taxes and other policies (28) or the potential effect of other regulations implemented by the Government such as the regulation of unhealthy food and beverages in schools and partial regulation of marketing targeted to children (29, 30). Conversely, an increase in industry strategies (campaigns, promotions, marketing) in the post-tax period (31) may have attenuated the true independent effect of the tax.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing body of research has documented the vast amount of marketing for nutritionally poor food and drinks aimed at children and its harmful impact on their diets and health. Therefore, public health experts propose regulations to limit unhealthy food marketing to children, also citing limitations of existing industry self‐regulatory program. In addition to advertising healthy food to children, experts also call on the food industry to promote nutrition and physical activity messages in food advertising to children as a potential solution.…”
Section: Introductionmentioning
confidence: 99%